1992
DOI: 10.1002/mpo.2950200407
|View full text |Cite
|
Sign up to set email alerts
|

13‐cis‐retinoic acid (NSC 122758) in the treatment of children with metastatic neuroblastoma unresponsive to conventional chemotherapy: Report from the childrens cancer study group

Abstract: The Childrens Cancer Study Group evaluated daily oral 13-cis-retinoic acid to determine its therapeutic efficacy in 28 children with advanced neuroblastoma refractory to conventional therapy. Cheilitis and fissured lips were the most common side effects; however, fewer than 50% of the patients experienced any toxicity. Two of twenty-two evaluable children demonstrated positive response to therapy. In one case, a child received the drug for 11 months. Seventeen patients demonstrated progressive disease within 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
59
0
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 9 publications
2
59
0
2
Order By: Relevance
“…61 Based on observations that RA can also induce differentiation of neuroblastoma cell lines in vitro, 16 -18 RA has been used for several clinical trials in neuroblastoma patients with variable results. [37][38][39][40] However, a recent study using high-dose 13-cis RA treatment after myeloablative therapy and autologous bone marrow transplantation showed encouraging results. 41 Since differentiation and/or growth arrest induced by RA, TPA or vitamin D 3 was shown to be potentiated by IFN-␥ in several cell types, [42][43][44][45][46][47] the aim of our investigation was to determine whether IFN-␥ would synergize with RA or TPA to induce differentiation and growth inhibition in neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…61 Based on observations that RA can also induce differentiation of neuroblastoma cell lines in vitro, 16 -18 RA has been used for several clinical trials in neuroblastoma patients with variable results. [37][38][39][40] However, a recent study using high-dose 13-cis RA treatment after myeloablative therapy and autologous bone marrow transplantation showed encouraging results. 41 Since differentiation and/or growth arrest induced by RA, TPA or vitamin D 3 was shown to be potentiated by IFN-␥ in several cell types, [42][43][44][45][46][47] the aim of our investigation was to determine whether IFN-␥ would synergize with RA or TPA to induce differentiation and growth inhibition in neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our results together with those of Wuarin et al 50 and a publication by Cornaglia et al, 48 reporting that combined therapy with RA and IFN-␥ inhibited tumor formation of LA-N-5 cells injected in nude mice, suggest that RA and IFN-␥ in combination may be of therapeutical interest. Presently both RA [37][38][39][40] and IFN-␥ 62 have been used as single agents in clinical trials for cancer therapy. This is a good basis for combination therapy with the 2 agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retinol derivative 13-cis-retinoic acid (13-cisRA) is now an established component of the treatment of high-risk neuroblastoma, despite the fact that early phase II trials conducted with low-dose 13-cisRA showed limited clinical benefit in patients with recurrent disease (Reynolds et al, 1991;Finklestein et al, 1992;Kohler et al, 2000). When 13-cisRA was administered as a highdose (160 mg m À2 day À1 ), intermittent regimen in a Children's Cancer Group phase III randomised trial, a significant improvement in 3-year event-free survival (EFS) was observed (Matthay et al, 1999).…”
mentioning
confidence: 99%
“…In addition to their well-established anti-carcinogenic activity [2,3,6,18], retinoids have been shown to inhibit the proliferation of a considerable number of cultured cells, including human and murine melanoma cells [8,15,16,19,24,27,28].…”
mentioning
confidence: 99%